Policy Feedback and Government Responsiveness in a~Comparative Perspective - Marius R. Busemeyer (Politische Vierteljahresschrift, 2022)
This paper focuses on the transferability of policy feedback and responsiveness theories. These theories have enjoyed a~great deal of scholarly interest in the past years and are widely applied in different country contexts. However, this theory transfer tends to be more focused on the empirical challenges while neglecting the fact that it also involves normative implications about representative democracy. These implications, I~argue, are strongly influenced by the real-world example of the United States, where the theories were originally developed. More specifically, I~contend that bringing in theoretical approaches that are more influenced by European experiences such as neocorporatism and party difference theory affects the depiction of the role of interest groups and party government in policy feedback and responsiveness theories. I~conclude by highlighting the contours of an empirical research agenda that might further elaborate on these issues.
Keywords: 320; USA; Germany; Corporatism; Party difference theory; Political inequality; USA; Deutschland; Korporatismus; Parteiendifferenztheorie; Politische Ungleichheit